2015
DOI: 10.3386/w21306
|View full text |Cite
|
Sign up to set email alerts
|

ICT and Education: Evidence from Student Home Addresses

Abstract: Governments are making it a priority to upgrade information and communication technologies (ICT) with the aim to increase available internet connection speeds. This paper presents a new empirical strategy to estimate the causal effects of these policies, and applies it to the questions of whether and how ICT upgrades affect educational attainment. We draw on a rich collection of microdata that allows us to link administrative test score records for the population of English primary and secondary school stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…7 Vigdor et al (2014) exploit local variations in broadband internet penetration in North Carolina to show that children who live in areas that receive additional internet providers experience a modest but significant decline in mathematics test scores (and insignificant decline in reading). Lastly, Faber et al (2016) exploit differences in broadband connection speeds across neighboring residences in England and find no significant impacts on test scores or time spent studying. However, to our knowledge, no previous study has separately identified the added effect of home internet access in an experimental setting.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…7 Vigdor et al (2014) exploit local variations in broadband internet penetration in North Carolina to show that children who live in areas that receive additional internet providers experience a modest but significant decline in mathematics test scores (and insignificant decline in reading). Lastly, Faber et al (2016) exploit differences in broadband connection speeds across neighboring residences in England and find no significant impacts on test scores or time spent studying. However, to our knowledge, no previous study has separately identified the added effect of home internet access in an experimental setting.…”
Section: Introductionmentioning
confidence: 96%
“…Brazil's Plano Nacional de Banda Larga. 3 SeeFairlie and Robinson (2013) andVigdor et al (2014) for evidence from the United States, andFaber et al (2016) for evidence from the United Kingdom. We discuss the findings from these studies in detail shortly.4 The XO laptops were developed by the One Laptop per Child (OLPC) program with an emphasis on self-empowered learning and with specialized software intended to encourage such learning.…”
mentioning
confidence: 99%
“…6 Vigdor et al (2014) exploit local variations in broadband internet penetration in North Carolina to show that children who live in areas that receive additional internet providers experience a modest but significant decline in mathematics test scores (and insignificant decline in reading). Lastly, Faber et al (2016) exploit differences in broadband connection speeds across neighboring residences in England and find no significant impacts on test scores or time spent studying. However, to our knowledge, no previous study has separately identified the added effect of home internet access in an experimental setting.…”
mentioning
confidence: 96%
“…Brazil's Plano Nacional de Banda Larga. 2 SeeFairlie and Robinson (2013) andVigdor et al (2014) for evidence from the United States, andFaber et al (2016) for evidence from the United Kingdom. We discuss the findings from these studies in detail shortly.…”
mentioning
confidence: 99%
“…Brazil's Plano Nacional de Banda Larga. 3 See Fairlie and Robinson (2013) and Vigdor et al (2014) for evidence from the United States, and Faber et al (2016) for evidence from the United Kingdom. We discuss the findings from these studies in detail shortly.…”
Section: Introductionmentioning
confidence: 99%